Becoming an Agile Software Architect - V, Rajesh (Packt Publishing, 2021)
A guide to successfully operating in a lean-agile organization for solutions architects and enterprise architects Key Features Develop the right combination of processes and technical excellence to address architectural challenges Explore a range of architectural techniques to modernize legacy systems Discover how to design and continuously improve well-architected sustainable software Book Description Many organizations have embraced Agile methodologies to transform their ability to rapidly respond to constantly changing customer demands. However, in this melee, many enterprises often neglect to invest in architects by presuming architecture is not an intrinsic element of Agile software development. Since the role of an architect is not pre-defined in Agile, many organizations struggle to position architects, often resulting in friction with other roles or a failure to provide a clear learning path for architects to be productive. This book guides architects and organizations through new Agile ways of incrementally developing the architecture for delivering an uninterrupted, continuous flow of values that meets customer needs. You'll explore various aspects of Agile architecture and how it differs from traditional architecture. The book later covers Agile architects' responsibilities and how architects can add significant value by positioning themselves appropriately in the Agile flow of work. Through examples, you'll also learn concepts such as architectural decision backlog, the last responsible moment, value delivery, architecting for change, DevOps, and evolutionary collaboration. By the end of this Agile book, you'll be able to operate as an architect in Agile development initiatives and successfully architect reliable software systems. What you will learn Acquire clarity on the duties of architects in Agile development Understand architectural styles such as domain-driven design and microservices Identify the pitfalls of traditional architecture and learn how to develop solutions Understand the principles of value and data-driven architecture Discover DevOps and continuous delivery from an architect's perspective Adopt Lean-Agile documentation and governance Develop a set of personal and interpersonal qualities Find out how to lead the transformation to achieve organization-wide agility Who this book is for This agile study guide is for architects currently working on agile development projects or aspiring to work on agile software deliv ...